Impact of COVID-19 on essential healthcare services in Addis Ababa, Ethiopia: Implications for future pandemics - Abera, A.; Fenta, E.H.; Woldehanna, B.T.; Wolde, F.B.; Legesse, M.; Regassa, L.D.; Mor, Siobhan M.; Kaba, M. (2024)
Background: Responding to the COVID-19 pandemic has presented an unprecedented challenge to health systems, with countries needing to balance the demands of responding directly to the pandemic, while simultaneously continuing provision of essential health services. This study aimed to explore the impact of COVID-19 on essential healthcare services in Addis Ababa, Ethiopia.